PENGEMBANGAN HANDOUT BERGAMBAR DENGAN KAMUS ISTILAH MATA PELAJARAN IPA SISWA TUNARUNGU SMALB - Hindam Wahaddyan; Saichudin Saichudin (Universitas Negeri Malang, 2014)
The objective of this development was a pictured Handout with term dictionary of Science learning for students in SMALB-B (Senior High School of Special Needs) YPTB Malang help the hearing impairment students in the 10th Grade semester II to understand concept and explore the environmental around that related their life. The development of this pictured Handout was adapted from the seven steps of Borg & Gall model (1983). Subject for product test is material expert, media expert, practitioner expert, user candidate, small group test, and large group test, where each group consists of 2 and 4 students in the 10th Grade SMALB-B YPTB Malang with pre-test and post-test. The development result showed Handout validity level. The research result from material expert was obtained score 94% (very feasible), media expert 99% (very feasible), practitioner expert 82% (very feasible), and for user candidate was obtained many scientific terms that still was not included in term dictionary. The result of small and large group test obtained the assessment of the product of pictured Handout with term dictionary of Science Subject was feasible to be used. Tujuan dari pengembangan ini dihasilkan digambarkan Handout dengan kamus istilah Ilmu Pengetahuan Alam pembelajaran bagi siswa SMALB-B (SMA Kebutuhan Khusus) YPTB Malang yang dapat meringankan siswa gangguan pendengaran di 10 kelas semester 2 dalam belajar memahami konsep dan menjelajahi sekitar lingkungan yang terkait dengan kehidupan. Pengembangan Handout membayangkan ini menyesuaikan langkah-langkah dari Borg & Gall Model (1983) yang terdiri dari 7 langkah. Hasil pengembangan menunjukkan tentang tingkat validitas Handout. Hasil penelitian dari ahli materi diperoleh skor 94% (sangat layak), ahli media 99% (sangat layak), ahli praktisi 82% (sangat layak), dan untuk calon pengguna yang diperoleh banyak istilah ilmiah yang masih belum dimasukkan ke dalam kamus istilah dan itu adalah daya tarik. Dari hasil kelompok kecil dan uji kelompok besar diperoleh penilaian terhadap produk yang digambarkan Handout dengan kamus istilah Ilmu Pengetahuan Alam Subjek layak untuk digunakan